2018
DOI: 10.1159/000489768
|View full text |Cite
|
Sign up to set email alerts
|

Role of Field Staining in the Cytological Assessment of Intraoperative Surgical Specimens

Abstract: Objective: To study the role of Field staining in scrape smears for intraoperative cytological (IOC) diagnosis. Specimens were assessed for categorizing among benign and malignant lesions, lymph node status, and adequacy of surgical cut margins as per specimen. Technique, adequacy, and quality were assessed along with comparison of cytological diagnosis with final histopathological diagnosis obtained on routine hematoxylin and eosin-stained slides. Study Design: A prospective observational study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…13,18 The sensitivity of scrape cytology in present study were calculated as 93.3%. Several studies showed 90-100% sensitivity of scrape cytology results and confirms its effectiveness, 16,19,20 whereas in some cases it was less than 90%. 21 The specificity as shown in studies by Kshirsagar et al and Mosarrat et al 19,22 and Sharma et al 2021 was found to be 97-98.5% specific 21 as shown in Table 3.…”
Section: (2008) and Gupta Et Al (2012)mentioning
confidence: 75%
See 1 more Smart Citation
“…13,18 The sensitivity of scrape cytology in present study were calculated as 93.3%. Several studies showed 90-100% sensitivity of scrape cytology results and confirms its effectiveness, 16,19,20 whereas in some cases it was less than 90%. 21 The specificity as shown in studies by Kshirsagar et al and Mosarrat et al 19,22 and Sharma et al 2021 was found to be 97-98.5% specific 21 as shown in Table 3.…”
Section: (2008) and Gupta Et Al (2012)mentioning
confidence: 75%
“…Several studies showed 90-100% sensitivity of scrape cytology results and confirms its effectiveness, 16,19,20 whereas in some cases it was less than 90%. 21 The specificity as shown in studies by Kshirsagar et al and Mosarrat et al 19,22 and Sharma et al 2021 was found to be 97-98.5% specific 21 as shown in Table 3. Table 4 shows the accuracy of scrape cytology of different studies which ranges from 93 -99.1%.…”
Section: (2008) and Gupta Et Al (2012)mentioning
confidence: 75%